Bodies, Images and Identities. On Philosophy, Art and Social Transformation - Moreno Sainz-Ezquerra, Yera (2018)
This article proposes to approach the field of art as a possible space for social transformation. Focusing on the performative capacity of images, and on the articulation processes of subjects and identities, different artistic practices are presented that propose new visual narratives that subvert and transform hegemonic imaginaries about bodies, desire and identities from a feminist and queer perspective. From authors like Judith Butler or Chantal Mouffe and the theoretical articulation they make in relation to identity from an anti-essentialist perspective, certain concepts (such as performativity, reappropriation or citationality) will be retaken, which have allowed the reformulation of subjectivity in new political and social terms and have permeated the visual work of a diversity of contemporary artists. For this purpose, different proposals will be analyzed. These proposals, located in the field of visual arts and through various formats (such as photography or mural painting), have burst in recent years in the dominant imaginaries and have involved a restructuring of the symbolic landscape with regard to issues such as gender, raciality, sex, sexuality or desire.